Spiroergometrie – Schritt für Schritt - Semper, Hannes; Kühnelt, Paul; Seipp, Philip (DMW - Deutsche Medizinische Wochenschrift, 2019)
Cardiopulmonary Exercise Testing (CPET) is a non-invasive simultaneous measurement of the cardiovascular and respiratory system during exercise to assess a patient’s exercise capacity.It is used in a wide spectrum of clinical applications for the objective determination of functional capacity and impairment. Cardiopulmonary exercise testing involves measurements of respiratory oxygen uptake (VO2), carbon dioxide production (VCO2), and other cardiopulmonary and metabolic measures during a symptom‐limited exercise test.This article gives an overview of indications and contraindications and explains step by step how cardiopulmonary exercise testing is being performed.
Keywords: Spiroergometrie; Belastungsuntersuchung; kardiopulmonale Funktionsdiagnostik